Kebangkitan Pendidikan Islam Pasca-Mongol - Siregar, Hamdan (LPPM IAI PERSIS GARUT, 2025)
This study looks at how Islamic education came back after the Mongol invasions, a time when schools, books, and scholars were majorly messed up. It's important to know how Muslim scholars and schools got things back on track after such big social and political problems. Using library research, the information came from articles, books, and historical studies from 2015 to 2025. By looking at the main ideas, the study finds three main things: schools were rebuilt, scholars started traveling again, and intellectual traditions were recreated with help from new rich people. The study shows that getting back on track after the Mongols wasn't easy or the same everywhere. It was a complicated process that helped Islamic scholarship become even stronger